2018
DOI: 10.1111/jcpe.12870
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution dental magnetic resonance imaging for planning palatal graft surgery—a clinical pilot study

Abstract: Palatal masticatory mucosa thickness measured by high-resolution, non-contrast enhanced dental MRI is comparable with that obtained by bone sounding. Dental MRI enables reliable, non-invasive and radiation-free planning of palatal tissue harvesting and can also be used for location of the GPA at 85% of measurement points, which might help reduce complications during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Along with recent technical advances (Flügge et al., 2016; Hilgenfeld, Prager, et al, 2018; Prager et al., 2015; Sedlacik et al., 2016), in vivo application of three‐dimensional (3D) dental magnetic resonance imaging (dMRI) has attracted growing interest in dentistry. This non‐ionizing dental imaging technique has already demonstrated high accuracy and reproducibility in 3D evaluation of periodontal soft tissues (Heil et al., 2018; Hilgenfeld, Kastel, et al, 2018) and peri‐implant bone defects (Hilgenfeld, Juerchott, et al, 2018). However, further research is needed to evaluate the clinical applicability of dMRI in the field of periodontology.…”
Section: Introductionmentioning
confidence: 99%
“…Along with recent technical advances (Flügge et al., 2016; Hilgenfeld, Prager, et al, 2018; Prager et al., 2015; Sedlacik et al., 2016), in vivo application of three‐dimensional (3D) dental magnetic resonance imaging (dMRI) has attracted growing interest in dentistry. This non‐ionizing dental imaging technique has already demonstrated high accuracy and reproducibility in 3D evaluation of periodontal soft tissues (Heil et al., 2018; Hilgenfeld, Kastel, et al, 2018) and peri‐implant bone defects (Hilgenfeld, Juerchott, et al, 2018). However, further research is needed to evaluate the clinical applicability of dMRI in the field of periodontology.…”
Section: Introductionmentioning
confidence: 99%
“…Dental magnetic resonance imaging (dMRI) is a promising new diagnostic tool in dentistry (Di Nardo, Gambarini, Capuani, & Testarelli, ) with potential fields of application in endodontics (Iohara et al, ), implantology (Duttenhoefer et al, ), orthodontics (Heil et al, ), and periodontology (Hilgenfeld et al, ). Recently, dMRI attracted attention for study of zirconia implants (Benic, Elmasry, & Hämmerle, ; Hilgenfeld et al, ), and excellent contrast and limited artifacts have been observed (Duttenhoefer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such direct nerve visualization may be beneficial for presurgical planning prior to implant dentistry but also prior to other procedures such as wisdom tooth removal or orthognathic surgery 8,28 . Within the context of implant surgery, MRI enables the measurement of mucosal thickness and may help planning of palatal tissue harvesting 41 . MRI may also enable postoperative evaluation of implants 18,19,42 and may offer the opportunity for detecting peri‐implant bone defects 3‐dimensionally 36 .…”
Section: Discussionmentioning
confidence: 99%